A method of constructing at least one 3 dimensional image. - O. K. Rahmat, Rahmita Wirza; Dimon, Mohd Zamrin; Khalil, Hassan Hadi; Mahmood, Ramlan; Mustafa, Norwati (2010)

(untitled)
A method of constructing at least one 3 dimensional image from plurality of data is provided, the method includes the steps of extracting data centerline using a center of gravity formula for at least one image, partitioning the at least one image into a plurality of portions, determining a plurality of gray scale points in each portion, compaing the plurality of gray scale points with a threshold value, determining the center of gravity for each portion and connecting a plurality of center of gravity. A 3 dimensional image (100) constructable from a plurality of data is also provided, the image (100) includes a plurality of 3 dimensional points linearly connectable to form at least one cloud of 3 dimensional points.